Characteristics and shelf-life of Corn Milk Yogurt - Supavititpatana P. (2014)
The chemical, physical and microbial characteristics, and shelf-lives of corn milk and cow milk yogurts were compared. Fat content of the corn milk yogurt was lower but protein content, hardness, consistency and counts of Streptococcus thermophilus and Lactobacillus delbrueckii subsp. bulgaricus were higher than those of the cow milk yogurt. In the sensory evaluation study, the appearance, color and flavor of both yogurts were not significantly different (P>0.05) at the end of 14 days of storage at 5°C. Fatty acid esters were not found in the cow milk yogurt while they were present as the main flavor compounds in corn milk yogurt. Shelf-lives of corn milk and cow milk yogurts were 14 days at 5°C. Results obtained suggest that corn milk is a potential raw material for making a novel yogurt.